Jejak Sejarah Kontribusi Hadrami dalam Bidang Pendidikan Dakwah di Kalimantan Selatan - Jamalie, Zulfa; Wibowo, Fasih (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2024)
This study explores the historical traces of the Hadrami community’s contribution to Islamic education and da'wah in South Kalimantan. The purpose is to examine and analyze the significant role of the Hadrami in spreading Islam, particularly through educational and cultural da'wah approaches in remote areas of the region.The research applies a descriptive qualitative method using sociological, anthropological, and historical approaches. These are integrated to investigate how the Hadrami contributed to Islamic propagation through da'wah networks, mosque establishment, halaqahs, and cultural assimilation with local communities.Findings reveal that Hadrami involvement in Islamic da'wah began as early as the time of Sunan Giri, and was strengthened by figures like Khatib Dayan and Sayid Ahmad Alaydrus. Their efforts extended beyond urban centers such as Banjarmasin and Martapura, reaching deep into the Dayak-inhabited highlands and rural areas like Hulu Sungai, Loksado, Hantakan, and Tanah Kusan. The Hadrami played a crucial role in the propagation and development of Islam in South Kalimantan through structured da'wah models and strong social networks. The study’s implication encourages further exploration of the Hadrami diaspora and suggests that their history in Kalimantan be considered an integral part of Hadrami heritage in Indonesia.